Properties of nano-silica-modified self-compacting engineered cementitious composites - Mohammed, B.S. (Elsevier Ltd, 2017)
An engineered cementitious composite (ECC) is a type of high-performance fibre-reinforced composite developed based on micromechanical principles. To improve the modulus of elasticity and minimise the drying shrinkage in self-compacting (SC) ECC without adversely affecting its ductility, nano-silica (NS) is included in the cementitious composite. Twenty SC-ECC mixtures were proportioned, cast, cured, and tested to determine the fresh and hardened properties by using two variables: polyvinyl alcohol (PVA) fiber and NS particles. Five levels of NS (0, 1, 2, 3, and 4) and four levels of PVA (0.5, 1, 1.5, and 2) were considered. A response surface methodology was used to conduct multi-objective optimisation and develop mix proportions that produce the best response to the compressive strength, modulus of elasticity, and energy absorption. It was found that mixtures with 2 PVA and 1.89 NS produce the most desirable responses. © 2017 Elsevier Ltd